Systematic review and classification of: Telemark Model: The road is made as we walk it together (1.ed.) - Halvorsen, Marianne Berg; Rustad, Kristen Buck (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2020)
Background: The Telemark Model is a course series designed to promote mental health and prevent social difficulties among children who have a learning disorder (i.e., mild intellectual disability [ID]). Courses are given when the child is in primary, secondary or high school. The form is psycho-educational, in which an exchange of information, advice and guidance on activities of daily living and meeting others in the same situation, is considered to contribute to increased coping and competence. This article describes the Telemark model offered to children who are diagnosed with a mild ID and their parents, following a diagnostic assessment at the neuropediatric rehabilitation clinic (HABU) at the Telemark Hospital Trust. The course series are given in separate groups where the children, youth and parents have their own course program. Topics in the courses are related to current life stages and deal with body, hygiene, leisure, friendship, puberty, work and support benefits. The intervention is developed by and operated by HABU Telemark Hospital Trust. Method: In addition to information from the founder of model, this review is based on a systematic literature search in several databases. The included databases were Embase, Medline og Psykinfo, NORART, Cochrane, Google Scholar, Cristin, NORA, Norart, SCOPUS, SweMed+, Cambell, NREPP, NICE, Blueprint, The Norwegian Electronic Health Library, CEBC portal of knowledge, The Danish “Metodeguiden” og CINAHL plus with Full Text. Results: The results in this paper consist of assessments of the intervention’s description, available studies, and quality of implementation. No studies of effect or evaluation of the model was identified in the literature search. In the available material there were no description of training of new personnel outside the Telemark Hospital nor any described strategy of implementation. Conclusion: Based on the criteria of Ungsinn, The Telemark Model is classified evidence level 1- well described interventions.